HIV/AIDS-Related Knowledge and Willingness to Participate in Voluntary Counseling and Testing among Health Sciences University Students - Ni Putu Wulan Purnama Sari; Anselmus Aristo Parut (Universitas Airlangga, 2018)
Introduction: Health sciences university students (HSUS) are susceptible to HIV infection due to frequent contact with patients whose HIV status is unknown. This study aimed to compare the HIV/AIDS-related knowledge and the willingness to participate in VCT among HSUS, analyzing the differences between groups, and correlation and effect between variables. Methods: This cross-sectional study involved 357 HSUS from the faculty of nursing, pharmacy, psychology and medicine at an accredited university. Samples were selected using simple random sampling. Data analysis used descriptive statistic, Pearson correlation, one-way ANOVA test, and linear regression test (α<0.05).Results: Most respondents were 20-21 years old single female who still live with parents, exposed to HIV/AIDS material twice/more via academic activities; lack of HIV/AIDS-related knowledge (51.5%), highest mean found in medical students (73.1%); willing enough to participate in VCT (83.5%), highest mean found in nursing students (86.4%). No correlation found between variables (p=0.101), and the regression model was not significant (p=0.101). HIV/AIDS-related knowledge contributed only 0.8% influence on the willingness to participate in VCT among HSUS (R2=0.008), other unidentified factors possibly play a more important role.Conclusion: Besides knowledge, other factors like demographic factors, social determinants, close person, health education, fear, and HIV-related stigma may affect the willingness to participate in VCT among HSUS. HSUS's knowledge about HIV/AIDS was low but their willingness to participate in VCT was quite high. HIV/AIDS-related knowledge has a slight contribution in determining HSUS's willingness to participate in VCT. Further analysis of other potential factors is needed to determine stronger predictors.